Determinants of Senior High School Tracks and Strands Inclination of Grade 10 Students of Buenavista II - Julius Monterde Virtudazo (East Asian Journal of Multidisciplinary Research, 2023)
The study accentuated on the determinants of senior high school tracks and strands inclination of Grade 10 students. It involved the 135 respondents of the three (3) secondary schools of Buenavista II.  The mean was employed to investigate the determinants of respondents’ inclination in Senior High School tracks and strands. Frequencies and Percentages were utilized to verify the respondents’ socio-demographic profile and tracks and strands preferences. The standardized survey questionnaire adopted from College Department of Don Bosco Technology Center was used to examine the senior high school preferences. Based on the findings of the study, majority of the respondents are aging 10-15 years and they are almost divided equally in terms of sex. Also, most of the parents are skilled workers and are high school graduates. Majority of the respondents have predilection on academic track. They rated high in personality as the basis in choosing tracks/stands. Also, they rated moderately high in family and relatives as factor.  Furthermore, they rated high in job opportunities and interest as indicators. On the other hand, only parents’ educational attainment significantly influenced students’ career preference. Based on the findings of the study, it is highly recommended that there must have an intensive career advocacy on parents and students for proper guidance